Performance analysis of the structural factors in the communication of the wireless sensor network - Ozyurt, Fatih; Avci, Engin; Cevik, Taner (Ieee, 2015)
Limited energy is one of the most important study issues for wireless sensor networks. Clustering alleviates this energy shortage problem by reducing the data traffic conveyed over the network. Researches have been proposed various clustering methods and have been put forward their methods by making serious assumptions and acceptions such as clusters near to the sink with smaller sizes. In this paper, we analyze the impact of various structural approaches such as the sizes of clusters, the node density, radio coverage.
Telsiz duyarga aglarln iletişiminde yaplsal faktorlerin performans analizi
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: wireless sensor network; clustering; energy conservations